IMPROVING CASE-BASED PEDIATRICS TEACHING METHODOLOGY THROUGH AN INTEGRATIVE APPROACH (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article examines the theoretical, methodological, and practical aspects of improving pediatric teaching through clinical cases and an integrative approach. The relevance of this topic is determined by the need to prepare future physicians for comprehensive clinical thinking, interdisciplinary analysis of a child's condition, and the selection of sound diagnostic, treatment, and preventive tactics, taking into account age-related, anatomical, physiological, psychological, pedagogical, and social factors. The role of the clinical case as an educational model combining fundamental knowledge, clinical disciplines, preventive pediatrics, communication skills, and an evidence-based approach is substantiated. A methodological structure for the lesson is proposed, including preliminary preparation, group discussion, interdisciplinary data interpretation, decision-making, reflection, and assessment of student competencies.